PENGARUH KONSENTRASI MOLARITAS KOH TERHADAP SIFAT KELISTRIKAN BIO BATERAI AMPAS KOPI - Pawarangan, Ishak; Tumewu, Widya Anjelia; Mawuntu, Vicky Julius; Kumendong, Igreya Mitchel; Pungus, Sayenne Givenshe (LPPM Politeknik Saint Paul Sorong, 2024)
Spent coffee grounds are an abundant organic waste material. Spent coffee grounds have significant potential as an environmentally friendly alternative energy source in bio-battery technology. This study aims to analyze the effect of KOH molarity concentration on the electrical properties of coffee ground-based bio-batteries. Variations in KOH molarity solutions of 1M, 3M, and 5M, each mixed with 50 grams of spent coffee grounds, were utilized to evaluate their effect on the electrical properties, including current, voltage, and power output. The results indicate that increasing the molarity concentration significantly enhances the bio-battery's performance, as evidenced by increased voltage and maximum power output. The highest electrical power output, 97.2 mW, was achieved at a 5M KOH concentration. The study concludes that selecting the appropriate molarity concentration is a key factor in optimizing the performance of coffee ground-based bio-batteries. This research contributes to the advancement of renewable energy development from organic waste.